Multi-modal detection methods based on vortex fluid device mediated red-emitting carbon dots for sensitive vitamin B6 detection in food - Yanan Yan; Hongping Zhang; Youhong Tang; Xuan Luo; Colin L. Raston; Ruyu Li; Shaomin Shuang; Chuan Dong (Food Chemistry, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Neodymium isotopes in marginal seawater trace continental weathering inputs - Zhaojie Yu; Zehua Song; Xiaojie Tang; David J. Wilson; Germain Bayon; Yi Huang; Xiaoying Kang; Hualong Jin; Shiming Wan; Christophe Colin (Geochimica et Cosmochimica Acta, 2026)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

A novel load testing method for condition assessment of network-level highway bridges using moving artificial truck fleets in an open traffic environment - Junyong Zhou; Qingpeng Zheng; Tang Tang; Bin Wei; Xiaoyi Zhou; Colin C. Caprani (Engineering Structures, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Guidance on selecting and evaluating AI auto-segmentation systems in clinical radiotherapy: insights from a six-vendor analysis - Branimir Rusanov; Martin A. Ebert; Mahsheed Sabet; Pejman Rowshanfarzad; Nathaniel Barry; Jake Kendrick; Zaid Alkhatib; Suki Gill; Joshua Dass; Nicholas Bucknell; Jeremy Croker; Colin Tang; et al. (Physical and Engineering Sciences in Medicine, 2025)
Artificial Intelligence (AI) based auto-segmentation has demonstrated numerous benefits to clinical radiotherapy workflows. However, the rapidly changing regulatory, research, and market environment presents challenges around selecting and evaluating the most suitable solution. To support the clinical adoption of AI auto-segmentation systems, Selection Criteria recommendations were developed to enable a holistic evaluation of vendors, considering not only raw performance but associated risks uniquely related to the clinical deployment of AI. In-house experience and key bodies of work on ethics, standards, and best practices for AI in Radiation Oncology were reviewed to inform selection criteria and evaluation strategies. A retrospective analysis using the criteria was performed across six vendors, including a quantitative assessment using five metrics (Dice, Hausdorff Distance, Average Surface Distance, Surface Dice, Added Path Length) across 20 head and neck, 20 thoracic, and 19 male pelvis patients for AI models as of March 2023. A total of 47 selection criteria were identified across seven categories. A retrospective analysis showed that overall no vendor performed exceedingly well, with systematically poor performance in Data Security & Responsibility, Vendor Support Tools, and Transparency & Ethics. In terms of raw performance, vendors varied widely from excellent to poor. As new regulations come into force and the scope of AI auto-segmentation systems adapt to clinical needs, continued interest in ensuring safe, fair, and transparent AI will persist. The selection and evaluation framework provided herein aims to promote user confidence by exploring the breadth of clinically relevant factors to support informed decision-making.

Vortex fluidic mediated generation of fatty acid ethyl esters from vegetable oils for applications in cosmetic emulsions - Xuejiao Cao; Xuan Luo; Amir Heydari; Safira M. Barros; Bradley Peter Kirk; Youhong Tang; Colin L. Raston (Journal of Cleaner Production, 2025)

Genomic determinants of biological age estimated by deep learning applied to retinal images - Yu Huang; Mohammad Ghouse Syed; Ruiye Chen; Cong Li; Xianwen Shang; Wei Wang; Xueli Zhang; Xiayin Zhang; Shulin Tang; Jing Liu; Shunming Liu; Sundar Srinivasan; et al. (GeroScience, 2025)
With the development of deep learning (DL) techniques, there has been a successful application of this approach to determine biological age from latent information contained in retinal images. Retinal age gap (RAG) defined as the difference between chronological age and predicted retinal age has been established previously to predict the age-related disease. In this study, we performed discovery genome-wide association analysis (GWAS) on the RAG using the 31,271 UK Biobank participants and replicated our findings in 8034 GoDARTS participants. The genetic correlation between RAGs predicted from the two cohorts was 0.67 ( P = 0.021). After meta-analysis, we found 13 RAG loci which might be related to retinal vessel density and other aging processes. The SNP-wide heritability ( h 2 ) of RAG was 0.15. Meanwhile, by performing Mendelian randomization analysis, we found that glycated hemoglobin, inflammation hemocytes, and anemia might be associated with accelerated retinal aging. Our study explored the biological implications and molecular-level mechanism of RAG, which might enable causal inference of the aging process as well as provide potential pharmaceutical intervention targets for further treatment. Graphical Abstract

Dosimetric comparison of proton therapy and CyberKnife in stereotactic body radiation therapy for liver cancers - Samuel Shyllon; Scott Penfold; Ray Dalfsen; Elsebe Kirkness; Ben Hug; Pejman Rowshanfarzad; Peter Devlin; Colin Tang; Hien Le; Peter Gorayski; Garry Grogan; Rachel Kearvell; et al. (Physical and Engineering Sciences in Medicine, 2024)
Stereotactic body radiation therapy (SBRT) has been increasingly used for the ablation of liver tumours. CyberKnife and proton beam therapy (PBT) are two advanced treatment technologies suitable to deliver SBRT with high dose conformity and steep dose gradients. However, there is very limited data comparing the dosimetric characteristics of CyberKnife to PBT for liver SBRT. PBT and CyberKnife plans were retrospectively generated using 4DCT datasets of ten patients who were previously treated for hepatocellular carcinoma (HCC, N = 5) and liver metastasis ( N = 5). Dose volume histogram data was assessed and compared against selected criteria; given a dose prescription of 54 Gy in 3 fractions for liver metastases and 45 Gy in 3 fractions for HCC, with previously published consensus-based normal tissue dose constraints. Comparison of evaluation parameters showed a statistically significant difference for target volume coverage and liver, lungs and spinal cord ( p < 0.05) dose, while chest wall and skin did not indicate a significant difference between the two modalities. A number of optimal normal tissue constraints was violated by both the CyberKnife and proton plans for the same patients due to proximity of tumour to chest wall. PBT resulted in greater organ sparing, the extent of which was mainly dependent on tumour location. Tumours located on the liver periphery experienced the largest increase in organ sparing. Organ sparing for CyberKnife was comparable with PBT for small target volumes.

The major uplift in Himalayas was no earlier than the Miocene: Evidence from marine sediment record in the Bay of Bengal - Zehua Song; Shiming Wan; Zhaojie Yu; Mingyang Yu; Christophe Colin; Yi Tang; Jin Zhang; Hualong Jin; Debo Zhao; Xuefa Shi; Anchun Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Orbital hydroclimate variability revealed by grain-size evidence in the tropical Pacific Islands since 140 ka - Xiaojie Tang; Zhaojie Yu; Zhengyao Lu; Lina Song; Zehua Song; Christophe Colin; Giuseppe Siani; Xiaoying Kang; Fengming Chang; Franck Bassinot; Shiming Wan (Global and Planetary Change, 2024)

Fish community traits near a large confluence: Implications for its nodal effects in the river ecosystem - Saiyu Yuan; Jiajian Qiu; Hongwu Tang; Lei Xu; Yang Xiao; Mengyang Liu; Colin Rennie; Carlo Gualtieri (Journal of Hydrology, 2023)

Acute noise is harmful on the anti-predator behaviour of commercially important juvenile coral reef fishes - Nathan William Price; Yijung Liu; Kao-Sung Chen; Cheng-Hao Tang; Chi-Fang Chen; Ming-Chung Cheng; Colin Kuo-Chang Wen (Behavioural Processes, 2023)

Expansion of C4 plants in South China and evolution of East Asian monsoon since 35 Ma: Black carbon records in the northern South China Sea - Mengjun Li; Shiming Wan; Christophe Colin; Hualong Jin; Debo Zhao; Wenqiang Pei; Wenjun Jiao; Yi Tang; Yang Tan; Xuefa Shi; Anchun Li (Global and Planetary Change, 2023)

Global transcriptomic profiles of circulating leucocytes in early lactation cows with clinical or subclinical mastitis - Zhangrui Cheng; Laura Buggiotti; Mazdak Salavati; Cinzia Marchitelli; Sergio Palma-Vera; Alistair Wylie; Haruko Takeda; Lijing Tang; Mark A. Crowe; D. Claire Wathes; Mark Crowe; Niamh McLoughlin; et al. (Molecular Biology Reports, 2021)

Identifying Potential Conflict Associated with Oil and Gas Exploration in Texas State Coastal Waters: A Multicriteria Spatial Analysis - Samuel D. Brody; Himanshu Grover; Sarah Bernhardt; Zhenghong Tang; Bianca Whitaker; Colin Spence (Environmental Management, 2006)